Dupilumab in the treatment of severe non-control broncial asthma - economic aspects - A. S. Salasyuk; M. Yu. Frolov; I. N. Barykina (Izdatelstvo OKI, 2019)
Severe non-control Bronchial Asthma (BA) is a sufficient social problem with decreasing of quality of life, high index of disability and death. New biological drug - dupilumab - would improve the situation.Materials and methods. Markov's model has been used for efficacy comparison of dupilumab and omalizumab with cycles between remissions and exacerbations of BA with interval as 4 weeks. Target population was 287naive patients per year which can be treated with dupilumab instead omalizumab. Non-direct comparison has shown that clinical efficacy of dupilumab was higher vs omalizaumab (prevention of 4,2 and 2,4 exacerbations/year accordingly, p<0,05). Horizon of budget impact analysis (BIA) was 3 years, and discounting rate was 5 %. Only direct costs were used (drugs' costs, expenditures due to hospitalizations and out-patients department treatment).Results. Cost of dupilumab was 1 013 012 RUR/patient/year, that less on 182,2 thsd RUR than in omalizaumab case (16,04 %). Dupilumab can reduce expenditures in frames of Governmental Guarantees Program on 58,3 mln. RUR for the first year, and 162,2 mln. RUR during 3 -years horizon (16,13 % saving). Direct costs reduction with dupilumab can explain by less expenditures on the cours of therapy as well as decreasing cost of hospitalization and out-patients cure.Conclusion. Hypothesis about possibilities of dupilumab inclusion into reimbursement programs has been confirmed from clinical-economic point of view.